Sources of Funds in Light Rail Transit Financing - Wuri Anny Yumantini; Ayomi Dita Rarasati; Jachrizal Sumabrata (IPTEK Journal of Proceedings Series, 2017)
The construction of Light Rail Transit (LRT) infrastructure requires a large amount of funding, larger than the existing Regional Budget (APBD), and therefore requires a funding scheme with high financial feasibility to cover this financial gap. This research is aimed at identifying and determining suitable sources and their respective proportion for such scheme using secondary data from literature study and records on the capacity of funding sources, and primary data from in-depth interviews, descriptive analysis and analysis on the capacity of each funding source. It is expected that the result of this research can identify feasible sources of funding and their proportion to be applied in the construction of LRT.